2022
DOI: 10.3390/agronomy12051119
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Introductions of Moniliophthora roreri from the Amazon to the Pacific Region in Ecuador and Shared High Azoxystrobin Sensitivity

Abstract: One of the main problems in the production of cacao in Ecuador is the disease caused by the fungus Moniliophthora roreri (frosty pod rot) which affects the pods. Here, we evaluate the genetic diversity of this fungus in Ecuador, and its sensitivity to the fungicide azoxystrobin. We evaluated 76 monosporic cultures from the Amazon and the Pacific coast regions. In vitro sensitivity assays tested several doses of the fungicide azoxystrobin to determine the percent of growth inhibition and the IC50. Concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Ecuador and Colombia are ideal countries for breeding resistance to FPR, considering the introduction of different strains of M. roreri in areas of intense cacao cultivation (Díaz‐Valderrama et al., 2022; Espinoza‐Lozano et al., 2022; Jaimes et al., 2016). For example, artificial inoculation of five cultivated clones with seven isolates of M. roreri in Colombia identified the hybrid ICS 95 (Amelonado × Criollo) as a resistant clone (Phillips‐Mora et al., 2005).…”
Section: Genetic Basis Of Agronomic Traitsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ecuador and Colombia are ideal countries for breeding resistance to FPR, considering the introduction of different strains of M. roreri in areas of intense cacao cultivation (Díaz‐Valderrama et al., 2022; Espinoza‐Lozano et al., 2022; Jaimes et al., 2016). For example, artificial inoculation of five cultivated clones with seven isolates of M. roreri in Colombia identified the hybrid ICS 95 (Amelonado × Criollo) as a resistant clone (Phillips‐Mora et al., 2005).…”
Section: Genetic Basis Of Agronomic Traitsmentioning
confidence: 99%
“…However, recent population analysis of M. roreri based on SSR and SNP markers identified six genetic clusters in areas of intense cultivation in tropical America: Four clusters represented Coastal Ecuador and three—Magdalena Valley in Colombia, and one cluster included both countries (Díaz‐Valderrama et al., 2022). Another study based on SSR markers identified high genetic variation in M. roreri from the Ecuadorian Amazon where three clusters were identified (Espinoza‐Lozano et al., 2022). A comparison of M. roreri collected from plantations in coastal Ecuador and a cluster representing Amazonia suggests the introduction of M. roreri from the Ecuadorian Amazon to Coastal Ecuador (Espinoza‐Lozano et al., 2022).…”
Section: Genetic Basis Of Agronomic Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The typical symptoms include abnormal shoots that display stem swellings, bud proliferation, and vegetative brooms, which inspired the name witches’ broom disease in cocoa [ 5 ]. The results of recent studies from the major cocoa-producing provinces of Ecuador showed that Moniliophthora species possess high morphological and genetic diversity [ 6 , 7 , 8 , 9 ]. For this reason, some alternatives such as cacao agroforestry systems [ 1 ] and biological controls using products based on endophytic organisms, including the combined application of natural or chemical products [ 10 ], have been used to reduce the impact of diseases, minimize the utilization of fungicides, and improve the yield of cocoa production.…”
Section: Introductionmentioning
confidence: 99%